Counseling on Good and Healthy Eating for “Jelita” Women (Approaching 50 Years) - Irma Muhsen; Ayu Sri Wahyuni; Andi Kamal M Sallo; Safriadi Darmansyah (Peneliti Teknologi Teknik Indonesia, 2023)
Ahead of the holy month of Ramadan, culinary tourism in the city of Makassar is enlivened with various festivals. The government also supports the implementation of food festivals through the